2011
DOI: 10.1111/j.1365-2923.2011.04035.x
|View full text |Cite
|
Sign up to set email alerts
|

The process of problem-based learning: what works and why

Abstract: We conclude that there is considerable support for the idea that PBL works because it encourages the activation of prior knowledge in the small-group setting and provides opportunities for elaboration on that knowledge. These activities facilitate the comprehension of new information related to the problem and enhance its long-term memorability. In addition, there is evidence that problems arouse situational interest that drives learning. Flexible scaffolding provided by cognitively and socially congruent tuto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
442
0
30

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(481 citation statements)
references
References 91 publications
(194 reference statements)
9
442
0
30
Order By: Relevance
“…Problem-based learning (PBL) is a student-centred pedagogy in which students learn about a subject through the experience of solving an open-ended problem found in trigger material. Even though PBL does not always bring a clear and defined solution to the problem, it allows for the development of desirable skills and attributes [12]. The major obstacles for implementation of PBL in higher education are lack of resources and competent academic staff facilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Problem-based learning (PBL) is a student-centred pedagogy in which students learn about a subject through the experience of solving an open-ended problem found in trigger material. Even though PBL does not always bring a clear and defined solution to the problem, it allows for the development of desirable skills and attributes [12]. The major obstacles for implementation of PBL in higher education are lack of resources and competent academic staff facilitation.…”
Section: Resultsmentioning
confidence: 99%
“…In the PBL-based curriculum, perception was even better because of the teaching organized around realistic clinical cases and students being active and cooperative learners. This could improve their perception of learning, of feeling confident in their academic success, and of being prepared to the exercise of their profession [13,25,27,38]. This could also enhance their social self-perception through repeated practice of group work [39].…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of PBL is that it promotes integration of knowledge and skills. Students not only acquire knowledge but also practice problem-solving skills, critical thinking, small group work and autonomous learning [25,26]. These constructivist learning environments are thought to influence positively students’ perception of their educational context and to foster deep learning [13,27].…”
Section: Introductionmentioning
confidence: 99%
“…To solve problems, students work in small groups to elaborate and negotiate ideas, and construct joint explanations (HmeloSilver, 2004;Schmidt et al, 2011). From an instructional design perspective, small group learning can achieve several important goals of PBL, for instance, constructing an extensive and flexible knowledge base, developing effective problemsolving skills, and becoming effective collaborators (HmeloSilver, 2004).…”
Section: Small Group Learning: Knowledge Co-construction or Informatimentioning
confidence: 99%
“…Since then, PBL has been adapted and researched in health professions education throughout the world (Barrows, 1988;Hmelo-Silver, 2004;Schmidt, 1989). In reflecting on why PBL works in health professions education, Schmidt, Rotgans, and Yew (2011) attributed its success to the following factors: the activation of prior knowledge in small group settings, opportunities for elaboration on this knowledge, the arousal of situational interest that drives learning, and the flexible scaffolding provided by "cognitively and socially congruent" tutors (p. 792). Many systematic reviews on PBL in health professions education found PBL to be equivalent or superior to more traditional curricula (e.g., Hartling, Spooner, Tjosvold, & Oswald, 2010;Neville, 2009).…”
Section: Introductionmentioning
confidence: 99%